Salmonella typhimurium necrotizing fasciitis: a case report - Radwan El Othman; Fatima Allaw; Antoine Kharsa; Souheil Hallit (Journal of Medical Case Reports, 2023)
Abstract Background Necrotizing fasciitis is an aggressive disease that causes necrosis in the muscular fascia and subcutaneous tissues. The infection spreads rapidly along the fascia and perifascial planes, followed by extension of the infection to nearby soft tissues and muscles. Necrotizing fasciitis can be attributed to different pathogens, namely Staphylococcus aureus, group A streptococci, and Clostridium perfringes. Only a few cases of skin and soft tissue infections from Salmonella species have been reported to date. Herein we report a case of Salmonella non-typhi necrotizing fasciitis, an exceedingly rare entity. This case report may serve as a potential management plan in similar cases in light of the scarcity of evidence. Case presentation A 20-year-old Caucasian male patient with congenital cardiac anomaly presented with diarrhea and unilateral lower extremity cellulitis causing septic shock. Cultures from blood and the bullae associated with the lower extremity cellulitis grew Salmonella typhimurium. Surgical debridement was performed. Intraoperative tissue cultures were positive for Salmonella typhimurium, and surgical pathology confirmed the diagnosis of necrotizing fasciitis. After a total of 6 weeks of appropriate antimicrobial therapy, another surgical debridement was executed for poor wound healing. New intraoperative cultures grew Fusarium species, and the patient received voriconazole with an adequate response. Immunologic studies showed humoral and cellular immunodeficiency. Conclusion It is important to maintain a high index of suspicion for rare entities that can cause skin and soft tissue infections, such as Salmonella non-typhi, in particular in immunosuppressed patients where a delay in diagnosis and management may have significant morbidity and mortality.